The Effects of Business Environments on Development : Surveying New Firm-Level Evidence - Xu, Lixin Colin (2012)
In the past decade, the World Bank has promoted improving business environments as a key strategy for development, which has resulted in a significant amount of investment in collecting firm-level investment climate surveys across countries. What lessons have emerged from the papers using these new data? The key finding is that the effects of business environments are heterogeneous and depend crucially on industry, initial conditions, and complementary institutions. Some elements of the business environment, such as labor flexibility, low entry and exit barriers, and a reasonable protection from the "grabbing hands" of the government, seem to matter a great deal for most economies. Other elements, such as infrastructure and contracting institutions (courts and access to finance), hinge on their initial status and the size of the market.